Pengaruh Kemandirian Belajar Dan Media Pembelajaran Dosen Terhadap Prestasi Belajar Akuntansi Sektor Publik Mahasiswa Pendidikan Akuntansi Universitas Muhammadiyah Surakarta Angkatan 2013 - Nurwati, Retno, Prof.Dr. H. Yetty Sarjono, M.Si (2015)
Retno Nurwati, A210110023. Accounting Education Program. Faculty of Teacher Training and Education. Universitas Muhammadiyah Surakarta, 2015. The purpose of this study was to determine: 1) Effect of independent learning on the learning achievement of public sector accounting, 2) Effect of learning media lecturer on the learning achievement of public sector accounting, 3) Effect of independent learning and learning media lecturer on the learning achievement of public sector accounting. This study includes quantitative research associative conclusions obtained based on the results of statistical analysis. The population in this study were all students of Universitas Muhammadiyah Surakarta Accounting FKIP force in 2013, amounting to 184 students with a sample of 119 students were taken by simple random sampling technique. The necessary data obtained through the questionnaire method and the method of documentation. Previously conducted research. Questionnaires have been tested and tested for validity and reliability were tested. Data analysis technique used is multiple linear regression analysis, t test, F test, the relative contribution and effective. Results of regression analysis regression equation: Y = 7,668+ 0,645x1 + 0,664x2 which means public sector accounting learning achievement is influenced by independent learning and learning media lecturer. The conclusion is: 1) There is significant influence independent learning the learning achievement of public sector accounting in accounting education students UMS angakatan 2013. Based on t test was obtained t_hitung> t_tabel ie 3.822>1.981 (α = 5%) and a significance value <0,05 is 0,000. 2) There is significant influence learning media lecturer on the learning achievement of public sector accounting in accounting education student generation UMS 2013. Based on t test was obtained obtained t_hitung> t_tabel ie 3.635> 1.981 (α = 5%) and a significance value <0.05 is 0.000 , 3) There is significant influence independent learning and learning media lecturer on the learning achievement of public sector accounting in accounting education students UMS force F 2013. Based on test results obtained F_hitung> F_tabel ie 29.202> 3.074 at a significance level of 5%. 4) variable x1 relative contribution of 50.9% and the effective contribution of 25.9%, the variable X2 relative contribution of 7% and the effective contribution of 7.6%. 5) The calculation of R ^ 2 was obtained 0.335, meaning 33.5% of public sector accounting learning achievement is influenced by independent learning and learning media lecturer, while the remaining 66.5% influenced by variables outside the research. Keywords: Independence Learning, Lecturer learning media, learning achievement